A Mathematical Model for a Hybrid Ignition System - Do, Quoc Am (Journal of Technical Education Science, 2023)
In the operation of a car’s ignition system, the primary ignition coil is responsible for generating a high voltage that typically ranges from around 100V to 300V. However, this self-induced electromotive force (emf) can lead to certain negative effects such as switch breakdown, inductive noise, and secondary voltage drop. This article introduces a novel hybrid ignition system designed for a 4-cylinder engine. This innovative system is a combination of capacitive discharge ignition system (CDI) and induction discharge ignition (IDI) system. The excess electromagnetic force energy (emf) generated during the induction ignition stage will be used in the capacitive ignition. Thereby contributing to limiting the negative effects as mentioned. Forming and solving the mathematical model for the hybrid ignition system mentioned above enables us to analyze the transient responses of the primary current (i1) and primary voltage (V1). These instantaneous responses are crucial in understanding the behavior of the composite ignition circuit and calculating key parameters such as ignition energy during the inductive and capacitive ignition stages, as well as the magnitude of the maximum secondary voltage (V2m). Furthermore, the article also presents experimental results from the hybrid ignition system to complement the theoretical analysis.